2003
DOI: 10.1046/j.1365-2265.2003.01815.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent concerns surrounding HRT

Abstract: SummaryMillions of women are treated with hormone replacement therapy (HRT) for relief of menopausal symptoms, including vasomotor flushes and sweats for which oestrogen is uniquely and highly effective. Others may continue longer-term treatment in the hope that HRT will help to prevent chronic disease. The preservation of bone mass with continuing oestrogen therapy and reduction of subsequent risk of fracture is well established. Observational studies of the metabolic and vascular effects of oestrogens have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 58 publications
0
18
0
1
Order By: Relevance
“…Even if a clear link has not yet been firmly established, recent reports have suggested that hormonal replacement therapy (HRT) could induce undesirable side effects (see review by Armitage et al 2003), which has led many patients to stop their HRT treatments. Natural hormones might, therefore, not be the best candidates as long-term adjuvants for antidepressant treatments, which would have to be administered presumably for several years to patients suffering from refractory depression.…”
Section: Discussionmentioning
confidence: 99%
“…Even if a clear link has not yet been firmly established, recent reports have suggested that hormonal replacement therapy (HRT) could induce undesirable side effects (see review by Armitage et al 2003), which has led many patients to stop their HRT treatments. Natural hormones might, therefore, not be the best candidates as long-term adjuvants for antidepressant treatments, which would have to be administered presumably for several years to patients suffering from refractory depression.…”
Section: Discussionmentioning
confidence: 99%
“…An important role for 17␀E in various aspects of skeletal growth and integrity is well known, and replacement therapy with native or synthetic ER modulators has historically been a potent adjunct to maintain bone mass and prevent fractures in postmenopausal women. Increased incidence of metabolic disease with certain ER modulators in nonskeletal tissues instills valid concerns, however, and may limit the use of some of these agents (34,35). ER modulators have complex direct and indirect effects on gene expression that can differ in part from 17␀E and often appear tissue restricted (6,36).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to genistein, an increase in the risk of breast cancer by estrogen treatment has been considered despite its protective effect on cardiovascular disease [29]. In addition, genistein is known to inhibit tyrosine kinase and has been reported to suppress proliferation of vascular smooth muscle cell(s) in an experimental model of hypertension [30,31,32].…”
Section: Discussionmentioning
confidence: 99%